Pediatric Klüver–Bucy Syndrome: Report of Two Cases and Review of the Literature - Juliá-Palacios, N.; Boronat, S.; Delgado, I.; Felipe, A.; Macaya, A. (Neuropediatrics, 2018)
Klüver–Bucy syndrome (KBS) is a rare behavioral phenotype described in monkeys and humans that appears most often after bilateral temporal damage. The main features of KBS are compulsion to examine objects orally, increased sexual activity, placidity, hypermetamorphosis, visual agnosia, and amnesia. Cases in children are scarce, and the most frequently reported etiology is herpes encephalitis. Hyperorality (90%), hypersexuality (82%), and epilepsy (70%) were the most common features of the 51 cases reported in the literature to date. Carbamazepine, selective serotonin reuptake inhibitors (SSRIs), and neuroleptics have been used for symptomatic treatment with variable control. Corticosteroids or immunosupressive agents, such as rituximab, can be an option to use in some cases, according to etiology suspicion. Cognitive and behavioral disturbances after KBS are often severe, but improvement can occur over a long time and residual disabilities vary from major to fairly mild.We report two new encephalitis-associated pediatric patients and review all of the pediatric KBS cases in the literature to better describe the clinical features of this rare neurobehavioral condition.
Keywords: pediatric; Klüver–Bucy syndrome; epilepsy; behavior; amygdala; limbic